Perception of Work Environment and Well-being in Activity-based Office – Three-wave Longitudinal Study - Sirola, Pia; Haapakangas, Annu; Ruohomäki, Virpi (Nordic Journal of Working Life Studies, 2022)
Activity-based offices (ABOs) have become increasingly common. Yet, longitudinal studies investigating the effects of change are rare. This three-wave longitudinal study compared perceptions of privacy and office support, satisfaction with the work environment, and well-being in an organization that renovated private offices into an ABO (maintaining assigned desks). Questionnaires were administered four months before and eight and 21 months after the change. Data on 34 employees from the first and 21 from the second follow-up were analyzed. Privacy, perceived office support for work tasks, and work engagement decreased at both follow-ups. No effects were found on perceived office support for interaction or job satisfaction. Satisfaction with the work environment decreased at the eight-month follow-up. This study’s long follow-up demonstrated the negative effects of office redesign on the perception of privacy, support for work tasks, satisfaction with the work environment, and well-being.